2012
DOI: 10.1103/physrevlett.109.147202
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Change of the Spin State in a Manganese Phthalocyanine by Coordination of CO Molecule

Abstract: We show that the magnetic state of individual manganese phthalocyanine (MnPc) molecules on a Bi(110) surface is modified when the Mn2þ center coordinates to CO molecules adsorbed on top. Using scanning tunneling spectroscopy we identified this change in magnetic properties from the broadening of a Kondo-related zero-bias anomaly when the CO-MnPc complex is formed. The original magnetic state can be recovered by selective desorption of individual CO molecules. First principles calculations show that the CO mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 44 publications
5
111
0
1
Order By: Relevance
“…A change of the spin state from S=1 to S=1/2 upon CO coordination was observed for MnPc on Bi(1 1 0) [773]. TERS (cf.…”
Section: Coordination Of Carbon Monoxide (Co)mentioning
confidence: 84%
“…A change of the spin state from S=1 to S=1/2 upon CO coordination was observed for MnPc on Bi(1 1 0) [773]. TERS (cf.…”
Section: Coordination Of Carbon Monoxide (Co)mentioning
confidence: 84%
“…Similar to MnPc molecules adsorbed on Bi(110), its broadening is though to be a result of the hybridization with the substrate. 12 Interestingly, we found clear signature of how electronic correlations on the central 3d metal ion influence the overall electronic structure of the system. This is done by studying the MnPc energy levels once the central Mn atom is adsorbed on top of a defect, which may be view as a perturbation potential influencing the e-e-interaction.…”
Section: Introductionmentioning
confidence: 85%
“…Our choice was motived by the fact that transition metal phthalocyanines are representative of a broad class of planar metal-organic compounds where the presence of partially empty d orbitals in the central metal atom gives them interesting magnetic properties. [11][12][13] Bi 2 Te 3 , on the other hand, is a well studied TI characterized by a single Dirac cone centered around the Γ point which makes it a In fact, a slight distortion of the molecule's four-fold symmetry can already be recognized in the overview scan of 1(a). This is confirmed by the atomically resolved images reported in 1(b-d) which also show the inequivalent appearance of the axis, with the one aligned along a dense-packed rows of Te atoms appearing slightly brighter than the other.…”
Section: Introductionmentioning
confidence: 99%
“…8 Further theoretical studies on a single MnPc molecule sandwiched between two single walled carbon nanotubes reveal its nearly perfect spin filtering properties. 6 It was already shown that the high spin ground state of MnPc S = 3/2 can be changed to S = 1 by adsorption on Bi(110) surface, 9 or S = 1/2 by reaction with CO, 9 or O 2 . 10 A higher spin state of S = 5/2 can, on the other hand, be obtained by doping with alkali metals.…”
mentioning
confidence: 99%